2010
DOI: 10.1080/09613210903263007
|View full text |Cite
|
Sign up to set email alerts
|

Central heating thermostat settings and timing: building demographics

Abstract: Crucial empirical data (currently absent in building energy models) on central heating demand temperatures and durations are presented. This data is derived from the first national survey of energy use in English homes and includes monitored temperatures in living rooms, central heating settings reported by participants, along with building, technical and behavioural data.The results are compared to model assumptions with respect to thermostat settings and heating durations. Contrary to assumptions, the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(173 citation statements)
references
References 26 publications
11
154
2
Order By: Relevance
“…Programmed heating controls do not necessarily do what they are designed to do: result in lower maximum temperatures or shorter heating periods (e.g. Williams et al, 1985;Shipworth et al, 2010). Taking control away from the customer cannot be relied upon to improve the situation: it may actually entrench and legitimize highdemand practices, disengaging customers from any need to consider and question them (Strengers, 2008).…”
Section: A¡ordancesmentioning
confidence: 99%
“…Programmed heating controls do not necessarily do what they are designed to do: result in lower maximum temperatures or shorter heating periods (e.g. Williams et al, 1985;Shipworth et al, 2010). Taking control away from the customer cannot be relied upon to improve the situation: it may actually entrench and legitimize highdemand practices, disengaging customers from any need to consider and question them (Strengers, 2008).…”
Section: A¡ordancesmentioning
confidence: 99%
“…The data analysed in this paper are taken from the Carbon Reduction in Buildings Home Energy Survey (CaRB HES), the first national survey exclusively focused on energy use in English homes 1 that commenced in early 2007 (for details, see Shipworth et al, 2010). Households were selected by stratified random sample drawn from the postcode address file.…”
Section: Survey and Temperature Measurementsmentioning
confidence: 99%
“…Average estimated heating duration was 8.2 hours for weekdays and 8.4 hours for weekends. Importantly, the analysis of Shipworth et al (2010) revealed large variability in the data, in particular regarding heating demand temperature (standard deviation (SD) of 2.58C). For heating duration estimates the SD was 1.5 hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons for this decision is that several recent field studies have shown no significant savings in households using PTs compared to households using non-programmable thermostats. (Cross & Judd, 1997;Haiad, et al, 2004;Nevius & Pigg, 2000;Shipworth, et al, 2010) Some of these studies have been summarized in a document by Shiller in Table 4. A few argue that homes relying on programmable thermostats consumed more energy than those where the occupants set the thermostats manually (Sachs, 2004), especially with heat pumps (Bouchelle, Parker, & Anello, 2000).…”
Section: Hold and Temperature Override Modesmentioning
confidence: 99%